Pengaruh pH terhadap Produksi Antibakteri oleh Bakteri Asam Laktat dari Usus Itik - Rudy Sutrisna; Christina Nugroho Ekowati; Edelina Sinaga Sinaga (Politeknik Negeri Lampung., 2015)
This study aimed to determine the effect of pH on the production of antibacterial by lactic acid bacteria. This study uses a completely randomized design factorial 3X 5 (3 X 5 treatment of bacterial isolates pH) with three replications. The first factor consisted of pH 4, pH 5, pH 6, pH 7, pH 8, and the second factor that isolates B2, B7, B8, whereas the parameters consists of a clear zone. The amount of production is determined by the size of the diameter of antibacterial inhibition zone against Salmonella sp. Differences in the production of antibacterial determined based on the results of analysis of variance. The treatment significantly further test BNT at 5% level. The results showed that the effect of media pH test based on the potential for the production of antibacterial effect. The diameter of the largest clear zone produced by B7 isolates at pH 6 was 17.2 mm, 17.1 mm B8 and B2 at pH 7 at 16.7 mm. The smallest diameter of the clear zone produced by B8 at pH 4 was 15.1 mm, B2 at pH 6 there is a clear zone of 12.7 mm and isolate B7 at pH 5 of 11.5 mm Keywords: Antibacterial, Lactic Acid Bacteria, pH, Salmonella sp, Clear zone